Feasibility of intraoperative neuromonitoring and cortical/subcortical mapping in patients with cerebral lesions of highly functional localizations—pathway to case adapted monitoring and mapping procedures - Staub-Bartelt, Franziska; Rapp, Marion; Sabel, Michael (Frontiers in Oncology, 2023)
Background Intraoperative neuromonitoring (IONM) and mapping procedures via direct cortical stimulation (DCS) are required for resection of eloquently located cerebral lesions. In our neurooncological department, mapping and monitoring are used either combined or separately for surgery of functional lesions. The study aims to provide a practical insight into strengths and pitfalls of intraoperative neuromonitoring and mapping in supratentorial functionally located infiltrating lesions. Methods IONM and mapping techniques performed in eloquent located brain tumors were analyzed with a focus on neurological outcome and resection results obtained via MRI. Additionally, the surgeons’ view on obligatory techniques was explored retrospectively immediately after surgery. To evaluate the impact of the described items, we correlated intraoperative techniques in various issues. Results Majority of the 437 procedures were performed as awake surgery (53%). Monopolar stimulation was used in 348 procedures and correlated with a postoperative temporary neurological deficit. Bipolar stimulation was performed in 127 procedures, particularly on tumors in the left hemisphere for language mapping. Overall permanent deficit was seen in 2% of the patients; neither different mapping or monitoring modes nor stimulation intensity, localization, or histopathological findings correlated significantly with permanent deficits. Evaluation of post-OP MRI revealed total resection (TR) in 209 out of 417 cases. Marginal residual volume in cases where total resection was assumed but MRI failed to proof TR was found (0.4 ml). Surgeons’ post-OP evaluation of obligatory techniques matched in 73% with the techniques actually used. Conclusion We report 437 surgical procedures on highly functional located brain lesions. Resection without permanent deficit was adequately achievable in 98% of the procedures. Chosen mapping or monitoring techniques mostly depended on localization and vascular conflicts but also in some procedures on availability of resources, which was emphasized by the post-OP surgeons’ evaluation. With the present study, we aimed to pave the way to á la carte choice of monitoring and or mapping techniques, reflecting the possibilities of even supratotal resection in eloquent brain tumor lesions and the herewith increased need for monitoring and limiting resources.